1993
DOI: 10.1002/lipi.19930950207
|View full text |Cite
|
Sign up to set email alerts
|

The Fatty Acids Composition of some Important Mediterranean Fish Species

Abstract: a t a n o s a n d A . N . S u g r e d o s *According to latest findings, the essentiality of w3-fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid ( D H A ) as micro nutrients as well as'their positive effect w.r.t. prevention and therapy of cardiovascular diseases can be considered as established facts. Since an adequate intake of €PA and D H A by humans via nutritional route is primarily limited to fish consumption. the current work was carried out to investigate the fatty acid composition of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
18
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 2 publications
10
18
1
Order By: Relevance
“…In this study, the analyzed specimens contained on average, only 1.23 l 0.35 g fat per 100 g edible part. In fish from the same area, the respective value was 3.45 l 2.94 g [13]. Therefore, the average concentration of EPA and DHA is 0.48 l 0.08 g/100 g edible part of the cephalopods and 0.65 l 0.54 g/100 g edible part of the fish.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In this study, the analyzed specimens contained on average, only 1.23 l 0.35 g fat per 100 g edible part. In fish from the same area, the respective value was 3.45 l 2.94 g [13]. Therefore, the average concentration of EPA and DHA is 0.48 l 0.08 g/100 g edible part of the cephalopods and 0.65 l 0.54 g/100 g edible part of the fish.…”
Section: Resultsmentioning
confidence: 97%
“…The sum of EPA and DHA varied from 33.69% to 46.30% of the total fatty acids. According to Zlatanos and Sagredos [13], the corre- sponding percentage in fish from the same geographical area is between 5.7% and 36.5%. Moreover, only 3 species among the 16 analyzed in that study had percentages of these fatty acids higher than 30%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipolytic activity was evaluated using cod liver oil since its composition is very similar to fatty acids of anchovies (Zlatanos and Sagredos, 1993). Cultures in Halobacterium medium supplied with 10% v/v cod liver oil were inoculated and incubated as usual for 10 days.…”
Section: Sarcoplasmic and Myofibrillar Proteins Extraction From Fishmentioning
confidence: 99%
“…Other studies showed that lipids are important trophic markers for the study of predator-prey relationships through the season; the fatty acid composition of the summer diet of fish species, characterised by the ingestion of small benthic organisms (Crustacea, Amphipoda and Decapoda, such as Natantia), is rich in DHA (Dalsgaard et al, 2003). This feed spectrum affects the fatty acids content of the fish meat, with previous papers reporting that tub gurnard contains more than 1 g of total-n-3-fatty acid per 100 g fresh fish (Zlatanos and Sagredos, 2006). Furthermore, the n-6/n-3 ratio and the Δ 5 -desaturase plus Δ 6 -desaturase index, used to estimate the long-chain n-6 and n-3 PUFA synthesis, confirmed the high content of polyunsaturated fatty acids; in particular, the Δ 5 -Δ 6 -desaturase index, related to flesh of tub gurnard analysed in all the seasons, showed lower activity compared to that determined in other fish species.…”
Section: Discussionmentioning
confidence: 99%